Pendampingan Penyusunan Laporan Keuangan dengan Teknik Pembukuan Sederhana pada Pelaku UMKM Scale-Up di Wilayah Tangerang Selatan - Dila Angraini; Tri Utami; Dea Annisa; Zulfa Rosharlianti; Wiwit Irawati (S1 Accounting Program, Universitas Pamulang, 2020)
Community service (PKM) with the Community Empowerment House (RPM) Institute South Tangerang. The purpose of this PKM is to assist in the preparation of MSME financial report bookkeeping with simple techniques using the Ms. program. Excel. The UKM players involved in this PKM maybe 50 people with online training and mentoring on November 26, 2020 through the Zoom Meeting. The methods used in this PKM are counseling or lectures, tutorials, discussions, mentoring, and assessment. The results of the PKM is helping MSME players in understanding the problems of bookkeeping and composing as well as calculating the Cost of Goods Sold and recording and calculating inventory more accurately, assisted by Ms. Excel. UMKM players are precise and disciplined in doing bookkeeping using the Ms. program. Excel. It is hoped that this PKM can be useful for various parties including MSME actors themselves, the Indonesian Accountants Association, the Government, and academics. <w:LsdException Locked=